Aesthetic rehabilitation of upper central incisors using combined direct and indirect technique: a case report - Muhamad Halil, Mohd Haikal; Mustafa, Muhammmad Hazwan; Kamaruzaman, Syahirah Aisyah (IIUM Press, 2022)
Improving dental appearances generally leads to an increase in confidence, social interactions and ultimately quality of life. This case aimed to perform aesthetic rehabilitation on the upper central incisors. The patient was a 25-year-old female who was concerned with the gap in her front teeth and discolouration of her crown. The treatment started with shade matching and preliminary measurements prior to cementation of temporary crown. Later, an all ceramic e.max Lithium Disilicate crown was cemented on tooth 11 followed by direct composite restoration on tooth 21 for diastema closure. In conclusion, both the indirect and direct restorative technique when applied appro